2016
DOI: 10.1159/000445500
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism in Allergic Disorders

Abstract: Allergic diseases such as asthma and rhinitis, as well the early phase of atopic dermatitis, are characterized by a Th2-skewed immune environment. Th2-type cytokines are upregulated in allergic inflammation, whereas there is downregulation of the Th1-type immune response and related cytokines, such as interferon-γ (IFN-γ). The latter is a strong inducer of indoleamine 2,3-dioxygenase-1 (IDO-1), which degrades the essential amino acid tryptophan, as part of an antiproliferative strategy of immunocompetent cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 110 publications
(144 reference statements)
3
51
0
2
Order By: Relevance
“…Indole and indole derivatives are mainly catabolized by the microbiota, and 5-HTP and KYN are produced by both the microbiota and the host cells. 13,14,16 Thus the decreased level of IAId, but not 5-HTP and KYN, on the skin surfaces of patients with AD indicates that Trp metabolism by the skin microbiota is attenuated, which is consistent with the metagenomics results obtained by Chng et al 18 and with our unpublished data.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indole and indole derivatives are mainly catabolized by the microbiota, and 5-HTP and KYN are produced by both the microbiota and the host cells. 13,14,16 Thus the decreased level of IAId, but not 5-HTP and KYN, on the skin surfaces of patients with AD indicates that Trp metabolism by the skin microbiota is attenuated, which is consistent with the metagenomics results obtained by Chng et al 18 and with our unpublished data.…”
Section: Discussionsupporting
confidence: 90%
“…However, KYN, 5-HTP, or IAA, the major metabolites of Trp, did not have any effects on the MC903-induced skin inflammation (see Fig E4, A-E, in this article's Online Repository at www.jacionline.org), although previous studies showed that some of the metabolites had inhibitory effects in various inflammatory conditions. [13][14][15] The interference of DMSO, the dissolvent of IAId, on the effect of MC903 was excluded because there was no difference between the mice treated with MC903 and those treated with MC903 plus DMSO (see Fig E4, F-J).…”
Section: Topical Iaid Attenuated the Mc903-induced Ad-like Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, measuring the serum levels of these metabolites provides comprehensive information on KP activity. In addition, the KYN to Trp ratio (KYN/Trp) is used widely to estimate the TDO and IDO activity . Table A lists the serum levels of these metabolites, as measured by LC‐MS and expressed in relative units corresponding to chromatographic peak areas, in healthy controls and patients with compensated cirrhosis, AD, and ACLF.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the KYN to Trp ratio (KYN/Trp) is used widely to estimate the TDO and IDO activity. (20) Table 1A lists the serum levels of these metabolites, as measured by LC-MS and expressed in relative units corresponding to chromatographic peak areas, in healthy controls and patients with compensated cirrhosis, AD, and ACLF. In patients with compensated cirrhosis, the KP activity was not significantly different from healthy controls.…”
Section: Kp Is Activated In Patients With Ad and Aclfmentioning
confidence: 99%